Shigella sonnei Bacteremia Presenting with Profound Hepatic Dysfunction - Oluwaseun Shogbesan; Andrew Rettew; Bilal Shaikh; Abdullateef Abdulkareem; Anthony Donato (Case Reports in Gastrointestinal Medicine)
Worldwide, Shigellosis is a significant public health issue, associated with nearly one million deaths annually. About half a million cases of Shigella infection are reported annually in the United States. Shigella bacteremia is uncommon and generally seen in children and immunocompromised adults. We present a case of a Shigella sonnei bacteremia with marked hepatic derangement in a 27-year-old previously healthy homosexual male with history of Roux-en-Y gastric bypass, who presented to the emergency room with a 4-day history of loose watery stool, abdominal cramps, nausea and vomiting, and yellow skin of 2-day duration. He reports similar diarrhea illness in two close contacts in preceding days. On examination, he was fully oriented but dehydrated, icteric, and febrile. Laboratory data revealed WBC of 2200/μL, elevated AST and ALT (201 IU/L, 73 IU/L resp.), normal alkaline phosphatase, elevated total and direct bilirubin of 8.2 mg/dL and 4.4 mg/dL, albumin of 3.2 g/dL, INR of 2.9, prothrombin time of 31.7, and platelet of 96,000/μL. Workup for infectious, autoimmune and medication-induced hepatitis, Wilson’s disease, and hemochromatosis was negative. Abdominal ultrasound and computed tomography of the abdomen showed hepatic steatosis and right-sided colitis. Stool and blood cultures were positive for Shigella sonnei. He was treated with ciprofloxacin with improvement in liver function. Follow-up blood test 4 months later was within normal limits.